Optimization of Guidance and Counseling Facilities and Infrastructure in Schools - Afdha Lianti; Neviyarni S; Yarmis Sukur (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
Facilities and infrastructure in the field of guidance and counseling have an important role in supporting the service process and interaction between counselors and clients. Optimization of facilities and infrastructure is considered an important step in increasing the effectiveness of guidance and counseling services. This study aims to explain the importance of optimizing guidance and counseling facilities and infrastructure in improving service quality and exploring its impact on interactions between counselors and clients. This study uses a literature review approach to collect and analyze various sources of information related to optimizing guidance and counseling facilities and infrastructure. Data from various articles, journals, and books relevant to the research topic were analyzed comprehensively. The results of the literature review indicate that optimizing guidance and counseling facilities and infrastructure can increase service efficiency, improve the counseling environment, and increase client satisfaction. In addition, adequate facilities and infrastructure also contribute to the creation of positive relationships between counselors and clients. From the literature review conducted, it can be concluded that optimizing guidance and counseling facilities and infrastructure is an important step in improving service quality and interactions between counselors and clients. Further research and practical implementation are needed to ensure the application of this optimization in the context of sustainable guidance and counseling.